Do Visionary-Feedback Seeking CEOs Enhance Firm Sustainability Through Eco-Innovation? A Moderated Mediation Model - Yuanyuan, Cheng; Yahya, Farzan; Waqas, Muhammad; Hongbo, Li (Frontiers in Psychology, 2022)
Based on upper echelons, paradox, and social capital theory, this study extends the association of CEO vision articulation and feedback-seeking behavior with firm sustainability by identifying the mediating role of eco-innovation and top management team (TMT) boundary-spanning behavior as a moderator. By analyzing the data of mid-sized to large Chinese firms using hierarchical regression and bootstrapping-based moderated path analysis, we found that product and process eco-innovation mediates the link between CEO vision articulation and firm sustainability while CEO feedback-seeking behavior enhances firm’s sustainability through product eco-innovation only. Finally, conditional indirect effects show the vital role of TMT boundary-spanning behavior in facilitating CEOs to improve the firm’s long-term sustainability through eco-innovation.